The sweat of their face : portraying American workers - Ward, David C., 1952-; Moss, Dorothy; Fagg, John, 1977- (Washington, DC : Smithsonian Books ; In association with the National Portrait Gallery, 2017)
"Published to accompany an exhibition at the National Portrait Gallery, Smithsonian Institution, Washington, DC"--Colophon.
Includes bibliographical references (pages 210-211) and index.
Complimentary copy from Dr. Sang Hoon Lee, Dean of Brac Business School, Brac University
Keywords: Working class in art -- Exhibitions; Working class -- United States -- Portraits -- Exhibitions; Portraits, American -- Exhibitions; ART / Collections, Catalogs, Exhibitions / General; ART / Subjects & Themes / Portraits; POLITICAL SCIENCE / Labor & Industrial Relations